Gender and age inequalities in regular sports participation: A cross-national study of 25 European countries - Van Tuyckom, C.; Scheerder, J.; Bracke, P. (Journal of Sports Sciences, 2010)
This article provides a unique opportunity to compare gender inequalities in sports participation across Europe, and the extent to which this varies by age using large, cross-sections of the population. The Eurobarometer Survey 62.0 (carried out in 2004 at the request of the European Commission and covering the adult population of 25 European member states, N = 23,909) was used to analyse differences in regular sports participation by gender and by age in the different countries. For the majority of countries, the occurrence of regular sporting activity was less than 40%. Additionally, binary logistic regression analyses identified significant gender differences in sports participation in 12 countries. In Belgium, France, Greece, Latvia, Lithuania, Slovakia, Spain, and the UK, men were more likely to report being regularly active in sports than women, whereas in Denmark, Finland, Sweden, and the Netherlands the opposite was true. Moreover, the extent to which these gender inequalities differ by age varies considerably across countries. The results imply that: (i) in some European countries more efforts must be undertaken to promote the original goals of the Sport for All Charter, and (ii) to achieve more female participation in sports will require different policy responses in the diverse European member states.